A preliminary investigation assessing the basic digital capabilities of minimally verbal children on the autism spectrum with intellectual disability. Issue 2 (15th July 2020) - Scholle, Petr; Herrera, Gerardo; Sevilla, Javier; Brosnan, Mark
Abstract : Purpose: Children with Autism Spectrum Disorder (ASD) can demonstrate a preference for using digital technologies which can represent a relative strength within the autism community. Such a strength would have implications for digitally mediated interventions and support for autism. However, research to date has not developed a methodology for assessing the capabilities of minimally verbal children on the autism spectrum with intellectual disability (ID) to use digital technology. Design/methodology/approach: Six minimally verbal children with ASD and ID undertook an accessible assessment that identified what capabilities for interacting with a digital tablet device they could and could not demonstrate. Twelve brief assessments were demonstrated, including turning on the device, adjusting the volume, operating the camera, touching, tilting and rotating the screen. Findings: Participants could be assessed on their digital capabilities. In this study, participants could largely touch and swipe the screen effectively and leave the app, but could not tilt and rotate the screen nor turn on the digital tablet device. Research limitations/implications: While the numbers were small, the findings indicate that the digital capabilities of this group can usefully be assessed. Future research can use such assessments to highlight how intervention effectiveness and support can be enhanced by matching the digital capacities of minimally verbal children with ASD and ID to technological support. This is a preliminary study and a greater understanding of children's prior experiences with technology will better inform how and which digital capabilities develop. Originality/value: This is the first study to assess a range of basic capabilities for using digital tablet devices in minimally verbal children with ASD and ID.